The Influence Of Education And Training On Teacher Performance At Global Islamic High School Surya Bandar Lampung - Rindi Setiarani; Iskandar Ali Alam (Cita konsultindo, 2024)
This research aims to find out influence education and training on teacher performance is to understand in more depth how education and training affects teacher performance and ultimately affects the quality of education provided to student. The selected population is all teachers who provide teaching at the Global Islamic High School Surya Bandar Lampung, consisting of 30 people, is considered representative and has characteristics relevant to the research objectives. Data collection is carried out through survey with a pre- designed questionnaire. After the data is collected, analysis is carried out using the device SPSS software, including multiple linear analysis, t test for hypothesis testing, F test, and closing with the coefficient of determination test to assess the strength of the relationship between variables. Based on studies theoretically and from the results of data analysis, it can be concluded that both partially and anova” Education and Training has a significant effect on Teacher Performance at Globar Surya Islamic High School Bandar Lampung